Synthesis Report of the Proceedings of the 10th Session of the State of the Nation Platform - Tabaire, Bernard; Okao, Jackie (ACODE, 2010)
A national budget is as good a place to start as any when one sets out to examine a country’s development priorities. That is what happened at the 10th State of the Nation Platform debate. The day’s topic was “Uganda’s National Budget 2010/2011: How Strategic are the Strategic Priorities?” Three panellists led off the discussion. They included Minister of State for Finance Hon. Fred Jachan Omach, Shadow Finance Minister Hon. Oduman Okello, and Uganda National Chamber of Commerce and Industry Chief Executive Officer Morrison Rwakakamba. Hon. Omach represented Hon. Syda Bbumba, the Minister of Finance, Planning and Economic Development. Hon. Fred Omach (with microphone), the Minister for Finance (General Duties), Hon. Oduman Okello, Shadow Mnisiter for Finance and Morrison Rwakakamba, UNCCI chief during the 10th session of the State of the Nation Platform held at Protea Hotel on July 2, 2010speech before Parliament. The theme of the budget was “Strategic Priorities to Accelerate Growth, Employment and Socio-Economic Transformation for Prosperity”. Now, long gone are the days when reading the budget in Uganda was a highly anticipated public event. Because the country has had a long period of macroeconomic stability with single digit inflation rates and a free foreign exchange regime, the presentation of the budget is just yet another state ritual. Virtually no new taxes are introduced these days. So it was surprising that a budget-related subject yielded an unusually lively debate. The discussion revolved around: • The necessity of the Pay As You Earn (PAYE) tax • Getting value for money • The place of agriculture in the national economy • Politics as a constraint to efficient planning The backdrop of the animated debate was the coming general election. Uganda will hold only its third general election under a multiparty dispensation in 30 years on February 2011. The debate therefore proceeded with participants looking into the budget to see whether it was aimed at making the wananchi happy so they will return the ruling NRM party to power. In short, was the 2010/2011 budget an election-year budget? It depends, of course, on how you read it. And how you read it depends in turn on where you sit, stand, lean, or squat politically. Whatever the case, this was one of the more substantive State of the Nation Platform debates todate.